2018
DOI: 10.1177/2158244018812620
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender Relations on Women’s Involvement and Experience in Climate Change Adaptation Programs in Bangladesh

Abstract: The nexus between poverty and climate change is a major concern, especially in a country like Bangladesh where lack of resources is a significant problem in both rural and urban areas. Climate change affects a wide demographic of the population in Bangladesh, and among those affected, women are more vulnerable to climate change impacts, as is evident from the history of climate-induced disasters in the country. Climate change increases women's socioeconomic vulnerabilities by directly impacting their family's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Bangladesh is a traditional patriarchal society. Deeply rooted unequal gender relations within states, political institutions and legal systems mean that males play a dominant role within families, communities and society as a whole (Tanjeela and Rutherford, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangladesh is a traditional patriarchal society. Deeply rooted unequal gender relations within states, political institutions and legal systems mean that males play a dominant role within families, communities and society as a whole (Tanjeela and Rutherford, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Abdullah et al (2011) characterize Bangladesh as having a collectivist culture that emphasizes group efforts, teamwork and group and family membership. Therefore the family-affiliated female director's role is to support the majority family or founder family interest, keep family secrets safe (Uddin and Choudhury, 2008) and make little contribution to the economic acumen of daily management decisions (Tanjeela and Rutherford, 2018). Nawaz and McLaren (2016, p. 19) argue that the Bangladeshi patriarchal society ensures that women keep silent and that their "silence is a conscious act to avoid conflict and protect family reputation".…”
Section: Women On Corporate Boards In Bangladeshmentioning
confidence: 99%
“…This view is also supported by the findings of Balikoowa et al [16]. Fortunately, in the event of a disaster occurring, the affected often work together irrespective of gender segregation to reduce the impact of the disaster [35]. recommendations of Odlum [24] who had suggested the use of smartphones in communication with the disaster management officials.…”
mentioning
confidence: 72%
“…Despite an emergent body of work on resilience, a notable absence exists in the understanding of women's roles in creating and sustaining resilience in the context of climate change [88]. Only a few studies were found that examined the relationship between gender and climate resilience in Bangladesh, for instance, the livelihood improvement of women [16] adaptation of agricultural technologies [77] and gender gap in farmers' weather-index insurance product preferences [65].…”
Section: Gender Inequalitymentioning
confidence: 99%
“…Therefore, initiating research in this area would generate significant policy implications. Little is known about how the existing climatic stressors are perceived and managed by the affected females in households, especially in the coastal areas of Bangladesh [88]. Hence, the overarching questions should include how coastal resilience is perceived from a gendered perspective, and what roles are played by women in creating and sustaining resilience at household, community and organisational levels.…”
Section: Gender Inequalitymentioning
confidence: 99%